Massachusetts Youth Screening Instrument for mental health needs of youths in residential welfare/justice institutions: identifying gender differences across countries and settings. Issue 5 (2nd September 2016) - Van Damme, Lore; Grisso, Thomas; Vermeiren, Robert; Guy, Laura; Verbeke, Lize; De Clercq, Barbara; Schmid, Marc; Vanderplasschen, Wouter; Colins, Olivier F.
Abstract: This study examines the use of the Massachusetts Youth Screening Instrument-Second Version (MAYSI-2) for mental health needs among 1643 youngsters in residential welfare/justice institutions in Europe and the USA, identifying gender differences across countries and settings. Overall, the MAYSI-2 appeared to be a reliable instrument among these youngsters, with only some scales falling (slightly) below the threshold of acceptable internal consistency. Girls (vs. boys) in Belgian/USA justice institutions and Swiss mixed welfare/justice institutions displayed higher scores for the angry–irritable, depressed–anxious, somatic complaints, suicide ideation scales. Also, detained girls from Belgium and Switzerland reported higher scores for traumatic experiences. No gender differences were revealed among adolescents in German welfare institutions. Our findings suggest that the MAYSI-2 may serve as a useful mental health screening instrument among youngsters in welfare/justice institutions and that girls in justice institutions and mixed welfare/justice institutions form a particularly vulnerable population with regard to mental health problems.